Characteristic of typical vegetation community and water use efficiency of dominant plants in desert steppe of Ningxia - HU Haiying; LI Huixia; NI Biao; SHI Bin; XU Dongmei; XIE Yingzhong (浙江大学学报. 农业与生命科学版, 2019)
The aim of this study was to provide a theoretical and technical basis for the selection and utilization of native grass by discussing the water use efficiency of dominant plants, and the vegetative characteristics of the Agropyron mongolicum, Glycyrrhiza uralensis and Stipa breviflora communities responding to different precipitation amounts in desert steppe of Ningxia. The field investigation and experiment were carried out; and carbon stable isotopic composition (δ13C) value, proline content and relative water content (RWC) of plant leaves were measured. The results showed that A. mongolicum, G. uralensis, S. breviflora and Lespedeza potaninii were the dominant species in the community with a large number of Artemisia scoparia, and they were all C3 plants. With the increase of precipitation amount during the rainy season, the species richness, diversity indexes of these three communities and the soil water content increased significantly. There were significant effects on the leaf δ13C value, proline content and relative water content due to different precipitation amounts, and had significant interaction with different species, indicating that there were significant differences among these five species. In comparison, the water-use efficiency of G. uralensis was the highest; the anti-dehydration ability of A. mongolicum was the stronger than that of the others; the osmotic regulation ability of L. potaninii and A. scoparia was strong; and the water-use efficiency of S. breviflora was stable. The δ13C value of dominant plants was with significantly negative correlation to the soil water content, and with significantly positive correlation to the proline content, as well as the relative water content of leaves. Overall, precipitation significantly affected the community species composition, structure, and water use efficiency of dominant plants. Glycyrrhiza uralensis had a more water-saving trait, while S. breviflora and A. scoparia exhibited a more ‘conservative’ water use pattern, and A. mongolicum and L. potaninii had a flexible water use pattern.